Evaluation and Development of Vancomycin Dosing Schemes to Meet New AUC/MIC Targets in Intermittent Hemodialysis Using Monte Carlo Simulation Techniques. (26th August 2020) - Lewis, Susan J.; Mueller, Bruce A.
Abstract: Published vancomycin dosing recommendations for patients receiving maintenance hemodialysis were not designed to meet newly recommended 24‐hour area under the curve/minimum inhibitory concentration (AUC24h /MIC) pharmacokinetic/pharmacodynamic targets. The aims of this study were to predict pharmacokinetic/pharmacodynamic target attainment rates with a commonly used vancomycin regimen and to design a new dosing scheme incorporating therapeutic drug monitoring (TDM) to maximize target attainment in patients receiving vancomycin and hemodialysis with high‐ or low‐flux hemodialyzers. Vancomycin pharmacokinetic‐ and dialysis‐specific parameters were incorporated into Monte Carlo simulations (MCS). A commonly used vancomycin regimen was modeled to determine its likelihood of attaining AUC24h /MIC targets for 1 week of thrice‐weekly hemodialysis treatments. MCS was then used to develop optimal initial vancomycin dosing for patients receiving intradialytic or postdialytic vancomycin administration with either high‐ or low‐flux hemodialyzers. Finally, a new MCS model incorporating TDM was built to further optimize the probability of pharmacokinetic/pharmacodynamic target attainment. Traditional vancomycin dosing methods are unlikely to meet AUC24h /MIC targets. Vancomycin doses necessary to attain AUC24h /MIC targets are significantly influenced by hemodialyzer permeability and whether vancomycin is administered intradialytically or after hemodialysis. Depending on dialyzer type and whether vancomycin is administered during or after hemodialysis, loading doses of 25 to 35 mg/kg followed by maintenance doses of 7.5 to 15 mg/kg are necessary to reach minimum AUC24h /MIC targets in 90% of virtual patients. For a 3‐day interdialytic period, a 30% higher maintenance dose is required to maintain target attainment. Dosing based on a single vancomycin serum concentration obtained prior to the second dialysis session greatly enhances the probability of target attainment.